Preparation process of high-purity polyferric sulfate
By using microporous concave and convex rod soil-supported sodium nitrite catalyst and macroporous molecular sieve to support sodium iodide and sodium chlorate cooxidant in the production of polymerized iron sulfate, the problems of high cost, low efficiency and environmental pollution in the prior art are solved, and the efficient preparation of high-purity polymerized iron sulfate is achieved.
Patent Information
- Application Number
- CN202411543434.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing production methods of polymeric iron sulfate have problems such as high production costs, poor product quality, low equipment efficiency and environmental pollution.
Microporous concave and convex rod soil is used to support sodium nitrite as catalyst, combined with macroporous molecular sieve to support sodium iodide and sodium chlorate as a cooxidant, to optimize the process parameters, promote catalytic reaction in the pore structure through oxidation reaction, and prepare high-purity polymerized iron sulfate.
The preparation of polymeric iron sulfate with tight structure and high purity is realized, which reduces the cost of oxidant use, increases the reaction rate and conversion rate, and the catalyst and co-oxidant are easily separated and can be reused.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flocculant preparation, and specifically relates to a preparation process of high-purity polymerized ferric sulfate. Background Art
[0002] Polyferric sulfate is an inorganic polymer coagulant with superior performance. Its morphology is a light yellow amorphous powdery solid, which is very soluble in water. A 10% aqueous solution is a reddish brown transparent solution. Polyferric sulfate solution is widely used in the purification of drinking water, industrial water, various industrial wastewater, urban sewage, sludge dehydration, etc.
[0003] There are three main methods for producing polyferric sulfate: direct oxidation, conversion oxidation and catalytic oxidation. The direct oxidation or conversion oxidation method for producing polyferric sulfate requires the consumption of a large amount of oxidant and excessive acid or alkali, resulting in high production costs, poor product quality, and difficulty in separation, which is not conducive to industrial promotion. At present, the catalytic oxidation method is widely used in the production of polyferric sulfate at home and abroad. Although the catalytic oxidation method is simple and easy to operate, the oxidation time is too long, the equipment efficiency is low, and the oxidation process often releases a large amount of nitrogen oxides, polluting the surrounding environment.
[0004] Patent CN116654991B proposes a production and processing technology for polyferric sulfate, which is obtained by mixing with perchlorate, sulfuric acid solution, and ammonium bicarbonate to react; the polyferric sulfate solid after production is efficiently dried and ground, which greatly improves the production efficiency and quality of polyferric sulfate powder.
[0005] Patent CN115818728A provides a method for preparing polyferric sulfate from a ferric sulfate solution, wherein iron ore is crushed into powder and sintered, activating the iron oxide while increasing the specific surface area of the powder, giving the powder surface a porous structure and shortening the production time of polyferric sulfate.
[0006] Patent CN105293589A provides a polyferric sulfate, which utilizes the characteristic that ferrous hydroxide is easily oxidized to ferric hydroxide by air under alkaline conditions, so that ferrous sulfate is converted into ferric hydroxide, and then an appropriate amount of sulfuric acid is added to polymerize for a certain period of time to obtain polyferric sulfate, but the oxidation efficiency and product quality need to be improved. Summary of the invention
[0007] The purpose of the present invention is to provide a preparation process of high-purity polyferric sulfate, wherein a modified catalyst is prepared by loading sodium nitrite on microporous attapulgite, sodium iodide and sodium chlorate are loaded on a macroporous molecular sieve as a co-oxidant, and process parameters are optimized to prepare polyferric sulfate with a compact structure and high purity.
[0008] In order to achieve the above object, the present invention provides the following technical solutions: A preparation process of high-purity polyferric sulfate comprises the following steps: S1: preparing an aqueous solution of ferrous sulfate heptahydrate, adding titanium dioxide waste sulfuric acid thereto, mixing, stirring, mixing and acidifying at a temperature of 90-110° C., to obtain a mixed solution A; S2: Preparation of microporous attapulgite-loaded sodium nitrite catalyst; S3: Preparation of mesoporous molecular sieves loaded with sodium iodide and sodium chlorate as co-oxidants; S4: adding the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reaction kettle, introducing oxygen, and reacting at a temperature of 70-90° C. for 1-3 hours to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the filter residue, and distill and concentrate to obtain the high-purity polyferric sulfate.
[0009] Furthermore, the process of preparing the ferrous sulfate heptahydrate aqueous solution in step S1 is: adding ferrous sulfate heptahydrate into water at a solid-liquid ratio of 1:10-15 by weight, and stirring at a temperature of 35-45° C. for 25-45 minutes.
[0010] Furthermore, in step S1, the molar ratio of the ferrous sulfate heptahydrate aqueous solution to the titanium dioxide waste sulfuric acid is 1:0.3-0.5; the reaction is stirred at a rate of 500 r / min for 30-50 min.
[0011] Furthermore, step S2 is specifically as follows: according to the solid-liquid ratio of 1:2-5, the microporous attapulgite is added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 30-40°C and 800-1000W for 15-25min; after washing and drying with distilled water, it is placed in a muffle furnace and calcined at a temperature of 400-500°C for 30-50min; then, a sodium nitrite aqueous solution accounting for 20-30% of the mass of the attapulgite is added, and ultrasonically treated at a temperature of 40-50°C and 1000-1200W for 10-20min; and calcined at 130-150°C for 10-15min to obtain a modified catalyst.
[0012] Furthermore, in step S2, the product is washed with distilled water, dried, placed in a muffle furnace, heated to 400-500° C. at a rate of 2-4° C. / min, and then kept warm and calcined for 30-50 minutes.
[0013] Furthermore, the particle size of the modified catalyst in step S2 is 10-20 nm.
[0014] Furthermore, step S3 is specifically as follows: prepare 0.2-0.5 mol / L sodium iodide aqueous solution and 0.5-1.5 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:5-10, and ultrasonically treat at a temperature of 40-60°C and 600-800W for 25-35min; then put it into a muffle furnace and roast it at a temperature of 150-180°C for 8-12min to obtain a modified oxidant.
[0015] Furthermore, the particle size of the modified pro-oxidant in step S3 is 60-100 nm.
[0016] Furthermore, in step S4, the modified catalyst and the modified oxidant account for 1-3% and 0.5-1% of the mass of the mixed solution A, respectively.
[0017] Furthermore, in step S5, the concentration is concentrated to a density greater than 1.6 g / cm 3 .
[0018] Attapulgite, also known as palygorskite or bentonite, is a natural silicate mineral with a unique rod-shaped crystal structure and abundant pores. Attapulgite has a wide range of applications in many fields due to its special physical and chemical properties. Attapulgite has a high specific surface area, usually between 100-300 m² / g; it has abundant pores, including micropores, mesopores and macropores; it has good adsorption properties and can adsorb a variety of organic and inorganic substances; the crystal structure of attapulgite is stable and not easily affected by acid, alkali and high temperature; it has a certain degree of expansion in water, but not as obvious as kaolin such as montmorillonite; it is usually weakly alkaline, with a pH value between 7.5-9.5.
[0019] Sodium nitrite (NaNO2) is an inorganic compound with a variety of uses, including food industry, chemical industry, medicine and water treatment. Sodium nitrite has strong oxidizing and reducing properties. Sodium nitrite can be prepared by a variety of methods, common methods include: Ammonia oxidation method: Principle: Ammonia is oxidized in the presence of oxygen to produce nitrous acid, and then reacts with sodium hydroxide to produce sodium nitrite. Sodium nitrate reduction method: Principle: Sodium nitrate is reduced to sodium nitrite under the action of a reducing agent (such as sulfur dioxide, hydrogen sulfide, etc.). Ammonium nitrite decomposition method: Principle: Ammonium nitrite decomposes at high temperature to produce sodium nitrite and ammonia.
[0020] Molecular sieves are a type of porous material with a regular pore structure that can selectively adsorb or separate molecules of different sizes and shapes. Molecular sieves are widely used in many fields such as chemistry, petroleum, natural gas, environmental protection, and medicine. The following is a detailed introduction to the basic information, types, physical and chemical properties, application fields, and preparation and regeneration methods of molecular sieves. Common types: zeolite molecular sieves, silica gel molecular sieves, activated carbon molecular sieves, etc.
[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are: The present invention utilizes microporous attapulgite loaded with sodium nitrite as a catalyst, utilizes the advantages of attapulgite such as large specific surface area, low cost, green environmental protection, and reusability, loads sodium nitrite solution, loads catalytic active components in the microporous structure, greatly reduces the use cost of the oxidant, improves the utilization rate, and has adsorption and decolorization efficiency; at the same time, utilizes macroporous molecular sieves to load sodium iodide and sodium chlorate as co-oxidants, and under the action of oxygen, acidified ferrous sulfate catalytically oxidizes to form polymerized ferric sulfate, which promotes the occurrence of catalytic oxidation reaction in the pore structure, shortens the reaction time, and improves the reaction rate, and has high reactant conversion rate and target product selectivity; the catalyst and the co-oxidant are both easy to separate and reusable, and have good practical significance. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The raw materials used in the present invention are as follows: Attapulgite was from Hubei Qifei Pharmaceutical Chemical Co., Ltd., item number QF2164; molecular sieve was from Shanghai Zhenzhun Biotechnology Co., Ltd., item number MS-10010.
[0024] A preparation process of high-purity polyferric sulfate in this embodiment comprises the following steps: S1: preparing an aqueous solution of ferrous sulfate heptahydrate, adding titanium dioxide waste sulfuric acid thereto, mixing, stirring, mixing and acidifying at a temperature of 90-110° C., to obtain a mixed solution A; S2: Preparation of microporous attapulgite-loaded sodium nitrite catalyst; S3: Preparation of mesoporous molecular sieves loaded with sodium iodide and sodium chlorate as co-oxidants; S4: adding the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reaction kettle, introducing oxygen, and reacting at a temperature of 70-90° C. for 1-3 hours to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the filter residue, and distill and concentrate to obtain the high-purity polyferric sulfate.
[0025] The process of preparing the ferrous sulfate heptahydrate aqueous solution in step S1 of this embodiment is as follows: adding ferrous sulfate heptahydrate into water at a solid-liquid ratio of 1:10-15 by weight, and stirring at a temperature of 35-45° C. for 25-45 minutes.
[0026] In step S1 of this embodiment, the molar ratio of the ferrous sulfate heptahydrate aqueous solution to the titanium dioxide waste sulfuric acid is 1:0.3-0.5; the reaction is stirred at a rate of 500 r / min for 30-50 min.
[0027] Step S2 of this embodiment is specifically as follows: according to the solid-liquid ratio of 1:2-5, the microporous attapulgite is added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 30-40°C and 800-1000W for 15-25min; after washing and drying with distilled water, it is placed in a muffle furnace and calcined at a temperature of 400-500°C for 30-50min; then, a sodium nitrite aqueous solution accounting for 20-30% of the mass of the attapulgite is added, and ultrasonically treated at a temperature of 40-50°C and 1000-1200W for 10-20min; and calcined at 130-150°C for 10-15min to obtain a modified catalyst.
[0028] In step S2 of this embodiment, the washed and dried material is placed in a muffle furnace, heated to 400-500° C. at a rate of 2-4° C. / min, and then kept warm and calcined for 30-50 minutes.
[0029] The particle size of the modified catalyst in step S2 of this embodiment is 10-20 nm.
[0030] Step S3 of this embodiment is specifically as follows: prepare 0.2-0.5 mol / L sodium iodide aqueous solution and 0.5-1.5 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:5-10, and ultrasonically treat them at a temperature of 40-60°C and 600-800W for 25-35min; then put them into a muffle furnace and roast them at a temperature of 150-180°C for 8-12min to obtain a modified pro-oxidant.
[0031] In step S3 of this embodiment, the particle size of the modified pro-oxidant is 60-100 nm.
[0032] In step S4 of this embodiment, the modified catalyst and the modified oxidant account for 1-3% and 0.5-1% of the mass of the mixed solution A, respectively.
[0033] In step S5 of this embodiment, the concentration is performed until the density is greater than 1.6 g / cm 3 .
[0034] Example 1 This embodiment provides a preparation process of high-purity polyferric sulfate, comprising the following steps: S1: Add ferrous sulfate heptahydrate to water at a solid-liquid ratio of 1:10, and stir at a rate of 500 r / min for 25 min at a temperature of 35°C to obtain a ferrous sulfate heptahydrate aqueous solution; mix the ferrous sulfate heptahydrate aqueous solution and titanium dioxide waste sulfuric acid at a molar ratio of 1:0.3, and stir at a temperature of 90°C at a rate of 500 r / min for 30 min to obtain a mixed solution A; S2: According to the solid-liquid ratio of 1:2, the microporous attapulgite was added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 30°C and 800W for 15 minutes; after washing with distilled water and drying, it was placed in a muffle furnace, heated to 400°C at a rate of 2°C / min, and then roasted for 30 minutes; then a sodium nitrite aqueous solution accounting for 20% of the mass of the attapulgite was added, and ultrasonically treated at a temperature of 40°C and 1000W for 10 minutes; and roasted at 130°C for 10 minutes to obtain a modified catalyst; S3: Prepare 0.2 mol / L sodium iodide aqueous solution and 0.5 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:5, and ultrasonically treat at a temperature of 40°C and 600W for 25 minutes; then put it into a muffle furnace and roast it at a temperature of 150°C for 8 minutes to obtain a modified oxidant; S4: Add the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reactor, wherein the modified catalyst and the modified oxidant account for 1% and 0.5% of the mass of the mixed solution A respectively; introduce oxygen, and react at a temperature of 70° C. for 1 hour to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the residue, and distill and concentrate until its density is greater than 1.6 g / cm 3 , the high-purity polyferric sulfate can be obtained.
[0035] Example 2 This embodiment provides a preparation process of high-purity polyferric sulfate, comprising the following steps: S1: Add ferrous sulfate heptahydrate to water at a solid-liquid ratio of 1:15, and stir at a rate of 500 r / min for 45 min at a temperature of 45°C to obtain a ferrous sulfate heptahydrate aqueous solution; mix the ferrous sulfate heptahydrate aqueous solution and titanium dioxide waste sulfuric acid at a molar ratio of 1:0.5, and stir at a temperature of 110°C at a rate of 500 r / min for 50 min to obtain a mixed solution A; S2: According to the solid-liquid ratio of 1:5, the microporous attapulgite was added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 40°C and 1000W for 25 minutes; after being washed with distilled water and dried, it was placed in a muffle furnace, heated to 500°C at a rate of 4°C / min, and then roasted for 50 minutes; then a sodium nitrite aqueous solution accounting for 30% of the mass of the attapulgite was added, and ultrasonically treated at a temperature of 50°C and 1200W for 20 minutes; and roasted at 150°C for 15 minutes to obtain a modified catalyst; S3: Prepare 0.5 mol / L sodium iodide aqueous solution and 1.5 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:10, and ultrasonically treat at a temperature of 60°C and 800W for 35 minutes; then put it into a muffle furnace and roast it at a temperature of 180°C for 12 minutes to obtain a modified pro-oxidant; S4: Add the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reactor, wherein the modified catalyst and the modified oxidant account for 3% and 1% of the mass of the mixed solution A respectively; introduce oxygen, and react at a temperature of 90° C. for 3 hours to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the residue, and distill and concentrate until its density is greater than 1.6 g / cm 3 , the high-purity polyferric sulfate can be obtained.
[0036] Example 3 This embodiment provides a preparation process of high-purity polyferric sulfate, comprising the following steps: S1: Add ferrous sulfate heptahydrate to water at a solid-liquid ratio of 1:12, and stir at a rate of 600 r / min for 35 min at a temperature of 40°C to obtain a ferrous sulfate heptahydrate aqueous solution; mix the ferrous sulfate heptahydrate aqueous solution and titanium dioxide waste sulfuric acid at a molar ratio of 1:0.4, and stir at a temperature of 100°C at a rate of 500 r / min for 45 min to obtain a mixed solution A; S2: According to the solid-liquid ratio of 1:3, the microporous attapulgite was added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 35°C and 850W for 22 minutes; after washing with distilled water and drying, it was placed in a muffle furnace, heated to a temperature of 450°C at a rate of 3°C / min, and then roasted for 40 minutes; then a sodium nitrite aqueous solution accounting for 25% of the mass of the attapulgite was added, and ultrasonically treated at a temperature of 45°C and 1150W for 16 minutes; and roasted at a temperature of 135°C for 12 minutes to obtain a modified catalyst; S3: Prepare 0.35 mol / L sodium iodide aqueous solution and 0.9 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:7, and ultrasonically treat at a temperature of 55°C and 750W for 28 minutes; then put it into a muffle furnace and roast it at a temperature of 165°C for 10 minutes to obtain a modified oxidant; S4: Add the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reactor, wherein the modified catalyst and the modified oxidant account for 2% and 0.8% of the mass of the mixed solution A respectively; introduce oxygen, react at a temperature of 85° C. for 2.5 hours, and obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the residue, and distill and concentrate until its density is greater than 1.6 g / cm 3 , the high-purity polyferric sulfate can be obtained.
[0037] Example 4. A preparation process of high-purity polyferric sulfate in this embodiment comprises the following steps: S1: preparing an aqueous solution of ferrous sulfate heptahydrate, adding titanium dioxide waste sulfuric acid thereto, mixing, stirring, mixing and acidifying at a temperature of 90-110° C., to obtain a mixed solution A; S2: Preparation of microporous attapulgite-loaded sodium nitrite catalyst; S3: Preparation of mesoporous molecular sieves loaded with sodium iodide and sodium chlorate as co-oxidants; S4: adding the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reaction kettle, introducing oxygen, and reacting at a temperature of 72° C. for 2 h to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the filter residue, and distill and concentrate to obtain the high-purity polyferric sulfate.
[0038] The process of preparing the ferrous sulfate heptahydrate aqueous solution in step S1 of this embodiment is as follows: adding ferrous sulfate heptahydrate into water at a solid-liquid ratio of 1:12 by weight, and stirring at a temperature of 38° C. for 27 minutes.
[0039] In step S1 of this embodiment, the molar ratio of the ferrous sulfate heptahydrate aqueous solution to the titanium dioxide waste sulfuric acid is 1:0.35; the reaction is stirred at a rate of 500 r / min for 35 minutes.
[0040] Step S2 of this embodiment is specifically as follows: according to the solid-liquid ratio of 1:3, the microporous attapulgite is added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 32°C and 900W for 20 minutes; after washing and drying with distilled water, it is placed in a muffle furnace and roasted at a temperature of 420°C for 35 minutes; then, a sodium nitrite aqueous solution accounting for 22% of the mass of the attapulgite is added, and ultrasonically treated at a temperature of 45°C and 1100W for 12 minutes; and roasted at 135°C for 12 minutes to obtain a modified catalyst.
[0041] In step S2 of this embodiment, the product is washed with distilled water, dried, placed in a muffle furnace, heated to 420° C. at a rate of 3° C. / min, and then kept warm and calcined for 35 minutes.
[0042] The particle size of the modified catalyst in step S2 of this embodiment is 12 nm.
[0043] Step S3 of this embodiment is specifically as follows: prepare 0.3 mol / L sodium iodide aqueous solution and 0.8 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:6, and ultrasonically treat them at a temperature of 48°C and 650W for 28 minutes; then put them into a muffle furnace and roast them at a temperature of 160°C for 9 minutes to obtain a modified oxidant.
[0044] In step S3 of this embodiment, the particle size of the modified pro-oxidant is 70 nm.
[0045] In step S4 of this embodiment, the modified catalyst and the modified oxidant account for 2% and 0.6% of the mass of the mixed solution A, respectively.
[0046] In step S5 of this embodiment, the concentration is performed until the density is greater than 1.6 g / cm 3 .
[0047] Example 4. A preparation process of high-purity polyferric sulfate in this embodiment comprises the following steps: S1: preparing an aqueous solution of ferrous sulfate heptahydrate, adding titanium dioxide waste sulfuric acid thereto, mixing, stirring, mixing and acidifying at a temperature of 90-110° C., to obtain a mixed solution A; S2: Preparation of microporous attapulgite-loaded sodium nitrite catalyst; S3: Preparation of mesoporous molecular sieves loaded with sodium iodide and sodium chlorate as co-oxidants; S4: adding the mixed solution A in step S1, the catalyst in step S2 and the co-oxidant in step S3 into a reaction kettle, introducing oxygen, and reacting at a temperature of 85° C. for 2 h to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the filter residue, and distill and concentrate to obtain the high-purity polyferric sulfate.
[0048] The process of preparing the ferrous sulfate heptahydrate aqueous solution in step S1 of this embodiment is as follows: adding ferrous sulfate heptahydrate into water at a solid-liquid ratio of 1:14 by weight, and stirring at a temperature of 42° C. for 28 minutes.
[0049] In step S1 of this embodiment, the molar ratio of the ferrous sulfate heptahydrate aqueous solution to the titanium dioxide waste sulfuric acid is 1:0.4; the reaction is stirred at a rate of 500 r / min for 45 minutes.
[0050] Step S2 of this embodiment is specifically as follows: according to the solid-liquid ratio of 1:4, the microporous attapulgite is added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 36°C and 860W for 20 minutes; after washing and drying with distilled water, it is placed in a muffle furnace and roasted at a temperature of 480°C for 48 minutes; then, a sodium nitrite aqueous solution accounting for 28% of the mass of the attapulgite is added, and ultrasonically treated at a temperature of 48°C and 1150W for 17 minutes; and roasted at 130-150°C for 14 minutes to obtain a modified catalyst.
[0051] In step S2 of this embodiment, the product is washed with distilled water, dried, placed in a muffle furnace, heated to 450° C. at a rate of 2-4° C. / min, and then kept warm and calcined for 40 minutes.
[0052] The particle size of the modified catalyst in step S2 of this embodiment is 12 nm.
[0053] Step S3 of this embodiment is specifically as follows: prepare 0.3 mol / L sodium iodide aqueous solution and 1.2 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:8, and ultrasonically treat them at a temperature of 55°C and 700W for 32 minutes; then put them into a muffle furnace and roast them at a temperature of 175°C for 10 minutes to obtain a modified oxidant.
[0054] In step S3 of this embodiment, the particle size of the modified pro-oxidant is 90 nm.
[0055] In step S4 of this embodiment, the modified catalyst and the modified oxidant account for 2% and 0.9% of the mass of the mixed solution A, respectively.
[0056] In step S5 of this embodiment, the concentration is performed until the density is greater than 1.6 g / cm 3 .
[0057] Comparative Example 1 The difference between this comparative example and Example 1 is that sodium nitrite is directly used in step S2, and the other steps are the same.
[0058] Comparative Example 2 The difference between this comparative example and Example 1 is that sodium iodide and sodium chlorate are directly used in step S3, and the other steps are the same.
[0059] Comparative Example 3 The difference between this comparative example and Example 1 is that the molar ratio of the ferrous sulfate heptahydrate aqueous solution to the titanium dioxide waste sulfuric acid in step S1 is 1:3, and the other steps are the same.
[0060] Comparative Example 4 The difference between this comparative example and Example 1 is that the microporous attapulgite in step S2 is not subjected to acidification treatment, and the other steps are the same.
[0061] Comparative Example 5 The difference between this comparative example and Example 1 is that only sodium iodide is loaded in step S3, and the other steps are the same.
[0062] Comparative Example 6 The difference between this comparative example and Example 1 is that in step S5, the mixture is concentrated to a density of 1.0 g / cm 3 .
[0063] Performance Test: According to GB / T14591-2016, the total iron content, reducing substances (Fe 2+ The results are as follows: Table 1 It can be seen from the above performance test results that Examples 1-5 have excellent performance in terms of reactant conversion rate and target product quality. In particular, the comprehensive performance of Example 3 is the most outstanding. However, since Comparative Examples 1-6 do not use necessary technical solutions such as modified catalysts and oxidants, their corresponding performance tests are significantly worse than those of the Examples. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0064] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A process for preparing high-purity polyferric sulfate, characterized in that: The steps include: S1: preparing an aqueous solution of ferrous sulfate heptahydrate, adding titanium dioxide waste sulfuric acid thereto, mixing, stirring, mixing and acidifying at a temperature of 90-110° C., to obtain a mixed solution A; S2: Preparation of microporous attapulgite-loaded sodium nitrite catalyst; S3: Preparation of mesoporous molecular sieves loaded with sodium iodide and sodium chlorate as co-oxidants; S4: adding the mixed solution A in step S1, the catalyst in step S2 and the oxidant in step S3 into a reaction kettle, introducing oxygen, and reacting at a temperature of 70-90° C. for 1-3 hours to obtain a mixed solution B; S5: Filter the mixed solution B in step S4 to remove the filter residue, and distill and concentrate to obtain the high-purity polyferric sulfate.
2. A process for preparing high-purity polyferric sulfate according to claim 1, characterized in that: The process of preparing the ferrous sulfate heptahydrate aqueous solution in step S1 is as follows: adding ferrous sulfate heptahydrate into water at a solid-liquid ratio of 1:10-15 by weight, and stirring at a temperature of 35-45° C. for 25-45 minutes.
3. A process for preparing high-purity polyferric sulfate according to claim 1, characterized in that: In step S1, the molar ratio of the ferrous sulfate heptahydrate aqueous solution to the titanium dioxide waste sulfuric acid is 1:0.3-0.5; the reaction is stirred at a rate of 500 r / min for 30-50 min.
4. A process for preparing high-purity polyferric sulfate according to claim 1, characterized in that: Step S2 is specifically as follows: according to the solid-liquid ratio of 1:2-5, the microporous attapulgite is added to a 0.5 mol / L hydrochloric acid aqueous solution, and ultrasonically treated at a temperature of 30-40°C and 800-1000W for 15-25min; after washing and drying with distilled water, it is placed in a muffle furnace and roasted at a temperature of 400-500°C for 30-50min; then, a sodium nitrite aqueous solution accounting for 20-30% of the mass of the attapulgite is added, and ultrasonically treated at a temperature of 40-50°C and 1000-1200W for 10-20min; and roasted at 130-150°C for 10-15min to obtain a modified catalyst.
5. A process for preparing high-purity polyferric sulfate according to claim 4, characterized in that: After being washed with distilled water and dried, the mixture is placed in a muffle furnace, heated to 400-500°C at a rate of 2-4°C / min, and then kept warm and calcined for 30-50 minutes.
6. A process for preparing high-purity polyferric sulfate according to claim 4, characterized in that: The particle size of the modified catalyst is 10-20 nm.
7. The process for preparing high-purity polyferric sulfate according to claim 1, characterized in that: Step S3 is specifically as follows: prepare 0.2-0.5 mol / L sodium iodide aqueous solution and 0.5-1.5 mol / L sodium chlorate aqueous solution respectively, and mix them; add molecular sieves thereto at a solid-liquid ratio of 1:5-10, and ultrasonically treat at a temperature of 40-60°C and 600-800W for 25-35min; then put it into a muffle furnace and roast it at a temperature of 150-180°C for 8-12min to obtain a modified oxidant.
8. A process for preparing high-purity polyferric sulfate according to claim 7, characterized in that: The particle size of the modified oxidant is 60-100 nm.
9. The process for preparing high-purity polyferric sulfate according to claim 1, characterized in that: In step S4, the modified catalyst and the modified oxidant account for 1-3% and 0.5-1% of the mass of the mixed solution A respectively.
10. The process for preparing high-purity polyferric sulfate according to claim 1, characterized in that: In step S5, the mixture is concentrated to a density greater than 1.6 g / cm 3 .
Citation Information
Patent Citations
Polymeric ferric sulfate
CN105293589A